1999
DOI: 10.1046/j.1365-294x.1999.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of amplified fragment length polymorphism (AFLP) in the isolation of sex‐specific markers

Abstract: Sex identification is a problem in research and conservation. It can often be solved using a DNA test but this is only an option if a sex-specific marker is available. Such markers can be identified using the amplified fragment length polymorphism (AFLP) technique. This is usually a taxonomic method, as it produces a DNA fingerprint of 50-100 PCR bands. However, if male and female AFLP products are compared, sex-specific markers are confined to the heterogametic sex and can rapidly be identified. Once a marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 11 publications
0
48
0
3
Order By: Relevance
“…; Mandolino et al 1999: Cannabis sativa; Korpelainen 2002: R. acetosa), mostly by combining bulked segregant analysis (Michelmore et al 1991) with random amplified polymorphic DNA (RAPD; Williams et al 1990). The procedure of the RAPD protocol is less time-consuming than AFLPs (Griffiths and Orr 1999). Moreover, AFLPs are much more costly in terms of laboratory equipment.…”
Section: Introductionmentioning
confidence: 99%
“…; Mandolino et al 1999: Cannabis sativa; Korpelainen 2002: R. acetosa), mostly by combining bulked segregant analysis (Michelmore et al 1991) with random amplified polymorphic DNA (RAPD; Williams et al 1990). The procedure of the RAPD protocol is less time-consuming than AFLPs (Griffiths and Orr 1999). Moreover, AFLPs are much more costly in terms of laboratory equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Amplified Fragment Length Polymorphism (AFLP) method has been used in ostrich (Struthio camels) and shag (Phalacrocorax aristotelis) to sex identification [26,27,28].…”
Section: Aflpmentioning
confidence: 99%
“…In Ratitae, SS and OSM 5 primers were used in sex identification of ostrich which belongs to Ratitae family [36,37]. PCR-based methods to sex-type ostriches were reported [28,36,38]. Identification of sex of the endangered old world vultures by PCR based method, facilitated the breeding of these birds in captivity [39].…”
Section: Chd Genes In Aviansmentioning
confidence: 99%
“…Evidence for type and/or presence of sex chromosomes is drawn from physical mapping of sex-specific sequences, from sex-linked linkage maps, from karyological studies and from crosses of sexreversed individuals (Legrand et al, 1987;Sagi and Cohen, 1990;Griffiths and Orr, 1999;Li et al, 2003;Parnes et al, 2003). In Crustacea of the order Decapoda, karyotype studies have revealed distinguishable sex chromosomes only in crabs (Brachyura) and hermit crabs (Anomura), as reviewed by Parnes et al (2003).…”
Section: Introductionmentioning
confidence: 99%